2000
DOI: 10.1002/1097-0290(20010205)72:3<346::aid-bit12>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost microbioreactor for high-throughput bioprocessing

Abstract: The design of a microbioreactor is described. An optical sensing system was used for continuous measurements of pH, dissolved oxygen, and optical density in a 2 mL working volume. The KLa of the microbioreactor was evaluated under different conditions. An Escherichia coli fermentation in both the microbioreactor and a standard 1 L bioreactor showed similar pH, dissolved oxygen, and optical density profiles.%The low cost of the microbioreactor, detection system, and the small volume of the fermentation broth pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
128
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(137 citation statements)
references
References 24 publications
5
128
0
4
Order By: Relevance
“…Currently, cellbased drug screening assays have been implemented for numerous molecular interactions, including ion channel activity (Denyer et al, 1998;Gonzalez et al, 1999), Gprotein-coupled receptor response (Conway et al, 1999), and induction of apoptosis (Lee et al, 2003). Multiplexed devices such as microtiter plates and array bioreactors have been developed for large-scale screening applications (Kostov et al, 2001;Maffia et al, 1999). While such advances have greatly improved throughput, limitations include high cost of operation and inability to continuously monitor cells over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, cellbased drug screening assays have been implemented for numerous molecular interactions, including ion channel activity (Denyer et al, 1998;Gonzalez et al, 1999), Gprotein-coupled receptor response (Conway et al, 1999), and induction of apoptosis (Lee et al, 2003). Multiplexed devices such as microtiter plates and array bioreactors have been developed for large-scale screening applications (Kostov et al, 2001;Maffia et al, 1999). While such advances have greatly improved throughput, limitations include high cost of operation and inability to continuously monitor cells over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, there is therefore a need to develop a microbioreactor that would address the following: process control, waste reduction, and high-throughput, speed-up testing, parallel investigation and optimisation. Previous work (Kostov et al 2001;Zanzotto et al 2004) has shown that microbioreactors provide unique environments, which are ideal for rapid and efficient biosynthesis due to the scale dependence of thermal and mass transfers.…”
Section: Introductionmentioning
confidence: 99%
“…The bioreactor's level of versatility in culturing different cell types is a determinant parameter. Mechanically stirred configurations such as those of Lamping et al (2003) and Kostov et al (2001) may not be suitable for shear-sensitive cells, such as animal and plant cells, and may perturb the coherence of the NMR magnetic field. An airlift bioreactor has also been used to study suspension plant cells (Fox et al, 1989).…”
Section: Introductionmentioning
confidence: 99%